Feasibility Analysis of Pancasila and Civic Education Textbooks in the 2013 Curriculum - Sukmawati Sukmawati; Jamaludin Jamaludin; Shofia Nurun Alanur; Kartini Kartini; Ade Ayu; Ahmad Gafar; Siti Fatima; Basran Basran; Era Era; Sartina Sartina; Ivon Ivon; Mita Mita; Nia Nia; Agil Agil; Ardi Ardi; Jesicca Jesicca; Isra Isra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to describe the feasibility of Class VII PPKn textbooks in the 2013 Curriculum in terms of content/material aspects, presentation based on a scientific approach, presentation based on authentic assessment, language, and graphics and the publication of Civics textbooks in accordance with the demands of the 2013 curriculum. Problems What is discussed in this study is the feasibility of teacher textbooks and Class VII PPKn student textbooks in the 2013 Curriculum at Madani Palu Integrated Model Public Middle School, using a qualitative research method with a descriptive research type. Research results show: (1) some aspects of the content/material in the teacher's textbook and student's textbook are appropriate in the 2013 curriculum and participation skills meet the eligibility standard, while citizenship knowledge, intellectual skills and civic character meet the eligibility standard (2) books teacher's texts and student textbooks in general are sufficient to encourage learning activities to be carried out with a scientific approach, (3) some aspects of the language are in accordance with the rules of Indonesian correctly, (4) some aspects of graphics have met the eligibility standards.